Audyt wewnętrzny, polityka rachunkowości a ryzyko działalności gospodarczej - Kwiecień, Mirosława (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The paper covers thinking in the scope of internal audit, accounting policy, and risk of economics. The Author has presented relations between actions (audit and accounting policy) and their influence on risk of economics. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1175, s. 190-197